2016
DOI: 10.1111/jcmm.12811
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of cullin 4A inhibits growth and increases chemosensitivity in lung cancer cells

Abstract: Cullin 4A (Cul4A) has been observed to be overexpressed in various cancers. In this study, the role of Cul4A in the growth and chemosensitivity in lung cancer cells were studied. We showed that Cul4A is overexpressed in lung cancer cells and tissues. Knockdown of the Cul4A expression by shRNA in lung cancer cells resulted in decreased cellular proliferation and growth in lung cancer cells. Increased sensitivity to gemcitabine, a chemotherapy drug, was also noted in those Cul4A knockdown lung cancer cells. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm. The cDNA was performed using 5 μg of total RNA, 200 U of Superscript III, and 0.5 μg of oligo dT (12)(13)(14)(15)(16)(17)(18) under the following conditions: 42˚C for 90 min, followed by heating at 70˚C for 10 min. The cDNA obtained was amplified using Taq DNA polymerase (Life Technologies) and Wt1 primers: 5'-AACGCCCCTTCATGTGTGC-3' and 5'-GCTGGTCTGAACGAGAAAACCTTC-3' to amplify a fragment of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA concentration and integrity were determined by measuring the absorbance at 260 nm. The cDNA was performed using 5 μg of total RNA, 200 U of Superscript III, and 0.5 μg of oligo dT (12)(13)(14)(15)(16)(17)(18) under the following conditions: 42˚C for 90 min, followed by heating at 70˚C for 10 min. The cDNA obtained was amplified using Taq DNA polymerase (Life Technologies) and Wt1 primers: 5'-AACGCCCCTTCATGTGTGC-3' and 5'-GCTGGTCTGAACGAGAAAACCTTC-3' to amplify a fragment of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, WT1 is considered a good target for anticancer therapy (12). The silencing of genes involved in proliferation and apoptosis are an attractive strategy for the development of anticancer therapies (13)(14)(15), and for sensitizing tumor cells to chemotherapy (14). It has been observed that silencing genes such as B-cell lymphoma 2 (BCL2) and BCL-xL sensitizes cisplatin-resistant cells (16,17).…”
mentioning
confidence: 99%
“…Furthermore, in vitro and in vivo studies showed decreased tumor growth and increased chemo-sensitivity to gemcitabine through G0/G1 cell cycle arrest after Cul4A (cullin 4A) knockdown, which is an important regulator of proliferation and cell cycle progression in lung cancer. In addition, Cul4A knockdown increases the expression of KLF10, cyclin-dependent kinase inhibitor p21/WAF1, and TGF-β1, which play a role as tumor suppressors [ 92 ].…”
Section: Role Of Klf10 As a Tumor Suppressor In Various Cancersmentioning
confidence: 99%
“…In esophageal cancer, secreted-TGFBI has been detected in the ECM and tumor vasculature by immunohistochemistry [ 37 ]. TGFBI expression is regulated not only by TGF-β, but also by other mechanisms including autophagy [ 38 , 39 ], microRNAs [ 40 ], retinoid [ 41 ], interleukin (IL)-1β, tumor necrosis factor-α [ 42 ], IL-4 [ 43 ], secreted protein acidic and rich in cysteine [ 44 ], 4-phenylbutyric acid [ 45 ], and cullin 4A [ 46 ] ( Figure 1 ). The mechanism of TGFBI regulation merits more detailed investigation as a potential therapeutic target.…”
Section: Role Of Tgf-β In Cancermentioning
confidence: 99%